2005
DOI: 10.4314/ajst.v5i1.15317
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Introducing and Implementing E-Learning for Delivery of Educational Content Within the African Context

Abstract: In Africa, where we have enormous and varied challenges in accessing higher education, there is need for relevant and customized content that is specific to our needs and challenges. Most of the models that exist to address these challenges have their limitations in terms of flexibility, time and space constraints and hence the need to address the mitigating factors. A blend of different types of information and communication technologies can be used in innovative ways in order to resolve some of these limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…Although several techniques (e.g., [9], [10], [11], [12], [13]) have been proposed, the issue of implementing an effective and efficient blended learning process in constrained low bandwidth environment has not been adequately addressed. In relation to this research, the process may include optimizing the multimedia performance in an attempt to develop the content relevant to the challenges of developing countries [31] and optimizing the network efficiency. And as such there is a significant need for a new technique [16] that addresses the above issue.…”
Section: Introductionmentioning
confidence: 99%
“…Although several techniques (e.g., [9], [10], [11], [12], [13]) have been proposed, the issue of implementing an effective and efficient blended learning process in constrained low bandwidth environment has not been adequately addressed. In relation to this research, the process may include optimizing the multimedia performance in an attempt to develop the content relevant to the challenges of developing countries [31] and optimizing the network efficiency. And as such there is a significant need for a new technique [16] that addresses the above issue.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by [2] focussed on the perceptions of Turkey academics about elearning. [18] had surveyed the perceptions of the faculty at the Manchester Metropolitan University in the United Kingdom and findings conform to existing literature that educators have a positive attitude towards e-learning systems [3], [2] compared to inflexible traditional teaching and learning paradigms [20], The few studies relating to Africa include [20] who observed that institutions in this environment lag in the use of ICT in education. This has been attributed to such factors as lack of institutional support, resources, information, knowledge and expertise to embrace e-learning technologies [18].…”
Section: Related Workmentioning
confidence: 90%
“…Nevertheless, aaffordances from the e-learning strategy yet to be realized in Zimbabwean and other similar contexts [20]. For example [5] studied the adoption of e-learning in developing countries and found that use of such widespread systems was still at its infancy.…”
Section: Related Workmentioning
confidence: 99%
“…Statistical projections indicate that enrolment for university education through e-learning was expected to grow consistently from about 900,000 in 2003 to about 15.2 million learners by the end of 2012 (MENON Network, 2007). The ability of new ICT facilities to support multimedia resource-based teaching and learning is fundamental to the growing interest in e-learning world over (Farahani, 2003;Omwenga, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical projections indicate that enrolment for university education through e-learning was expected to grow consistently from about 900,000 in 2003 to about 15.2 million learners by the end of 2012 (MENON Network, 2007). The ability of new ICT facilities to support multimedia resource-based teaching and learning is fundamental to the growing interest in e-learning world over (Farahani, 2003;Omwenga, 2004).Various terminologies are often used in place of e-learning, for instance, online learning, virtual learning, distributed learning, network, or web-based learning. Whatever the terminology used, the primary connotation is the application of ICT tools, including the internet to mediate asynchronous as well as synchronous teaching and learning activities (Naidu, 2006).…”
mentioning
confidence: 99%